The impact of financial leverage towards investment decision of construction firms in Malaysia / Shirley Jasni Changgai - Changgai, Shirley Jasni (2016)
This study has been conducted to determine the impact of financial leverage towards investment decision for Construction's sector that listed in Bursa Malaysia. Based on the previous research, there are some of researcher give an attention on the impact of financial sector on the failure of firm, such as bad financial management and insufficiency of capital. This study is conducted to test the impact of financial leverage towards investment decision of construction firm in Malaysia over the period 2006 until 2015. In this study, there are three independent variables and one dependent variable. Panel regression method is used for the data analysis. Result shows that debt ratio has a negatively significant towards investment decision while current ratio and sales growth have positively significant towards investment decision.